The Implementation of Merdeka Belajar Curriculum: Impact Toward Students’ Learning Outcomes at Islamic Middle School - Yuliana, Yuliana; Rustan, Rustan; Wisran, Wisran; Kartini, Kartini (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study intends to analyze the implementation of the Independent Curriculum and its impact on the learning outcomes of eighth-grade students in English at Islamic Middle School. This study uses a qualitative approach with data collection techniques through classroom observation, in-depth interviews, and documentation. This research was conducted at the Islamic Middle School As'adiyah Putra Sengkang. Data analysis was carried out using Michael Fullan's theory of educational change and Deci & Ryan's Self-Determination Theory (SDT) as a theoretical framework. The findings of the study indicate that the implementation of the Independent Curriculum at the madrasah has entered a solid implementation stage and is starting to move towards institutionalization. Teachers carry out differentiated learning, provide assignment choices, and create a learning environment that supports students' autonomy, competence, and social connectedness. As a result, students experience improved learning outcomes that cover three main domains: a) Cognitive domain: increased critical thinking skills, problem-solving, and in-depth conceptual understanding through contextual tasks and authentic assessments; b) Affective domain: the growth of intrinsic learning motivation, self-confidence, and a sense of responsibility for the learning process; c) Psychomotor domain: the development of presentation skills, collaborative work, and the production of creative work in various learning projects. This study recommends the need to strengthen teacher capacity and provide institutional support to maintain the consistent and sustainable implementation of the Independent Curriculum.